The Role Of Corporate Social Responsibility And Good Corporate Governance In Enhancing Financial Performance - Hapsari Amartha Pertiwi; Katiya Nahda (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the role of corporate social responsibility (CSR) disclosure and good corporate governance (GCG) in enhancing financial performance. This research model was tested using a sample from all mining sector companies listed on the Indonesia Stock Exchange during the period 2020-2022. The data analysis employed multiple linear regression and Generalized Least Square (GLS) methods to identify independent variables influencing the dependent variable in detecting indirect effects through financial performance proxied by ROA, EPS, and Tobin’s Q. The results of the study indicate that CSR has a positive effect on ROA, a negative effect on EPS, and no significant effect on Tobin’s Q. GCG proxied by independent board of commissioners, has a positive effect on ROA and Tobin’s Q. Audit committee has a positive effect on ROA and a negative effect on EPS and Tobin’s Q. Board of directors has a positive effect on EPS and Tobin’s Q but no significant effect on ROA.